2004
DOI: 10.1097/01.ta.0000052364.71392.70
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intrarater Reliability in Computed Axial Tomographic Grading of Splenic Injury: Why So Many Grading Scales?

Abstract: CT imaging is not reliable for identifying grades III and IV splenic injury, as experienced radiologists often underestimate the magnitude of injury. Interrater reliability is poor. Factors other than the CT grade of splenic injury should determine whether patients require operative or angiographic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…A recent study at this institution demonstrated the current AAST grading system has poor interrater reliability. 6 Other limitations of this investigation are the relatively small size of the validation group and the use a retrospective review of prospectively collected data. Because of the small validation sample, there are fairly wide confidence intervals about the point estimates for both sensitivity (85% to 100%) and specificity (72% to 95%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study at this institution demonstrated the current AAST grading system has poor interrater reliability. 6 Other limitations of this investigation are the relatively small size of the validation group and the use a retrospective review of prospectively collected data. Because of the small validation sample, there are fairly wide confidence intervals about the point estimates for both sensitivity (85% to 100%) and specificity (72% to 95%).…”
Section: Discussionmentioning
confidence: 99%
“…Our group found a high degree of intraand interrater variability in CT grading of splenic injury, even among highly experienced trauma radiologists. 6 The development of a clinically relevant screening test, relating patterns of injury present on CT scans with the need for intervention, should improve management and ultimately the outcome of patients with injury to the spleen. We present a clinical screening test based on CT imaging results and demonstrate its utility in a series of adults with splenic injuries.…”
mentioning
confidence: 99%
“…26 -28 In at least one study, computed tomography was found to underestimate the severity of the splenic injury found at operation, especially in distinguishing between grades III and IV. 26 Because the patients evaluated in the OR or AE groups were all studied with computed tomography, any bias or error in CT grading would be present across the spectrum. If computed tomography actually undergraded injuries in the AE patients compared with the OR patients as some suggest, the splenic injury grade may have been even higher.…”
Section: Discussionmentioning
confidence: 99%
“…Acquiring images that increase the conspicuity of both splenic active bleeding and nonbleeding vascular injury is essential to assess the true extent of anatomic disruption of the splenic parenchyma and vasculature, to grade the severity of injury accurately, and to aid important clinical decision making. Authors of prior studies (5,6,26) reported poor performance of CT for prediction of the need for intervention. These retrospective studies did not include the acquisition of arterial phase images and used pathologic or surgical reports to verify only parenchymal disruption or active bleeding but not nonbleeding vascular injury.…”
Section: Discussionmentioning
confidence: 98%